Optimizing pea protein fractionation to yield protein fractions with a high foaming and emulsifying capacity. (May 2022) - Kornet, Remco; Yang, Jack; Venema, Paul; van der Linden, Erik; Sagis, Leonard M.C.
Abstract: Specific pea protein fractionation steps can be used to control foaming and emulsifying properties of three pea protein fractions at pH 7.0. Mild fractionation, involving dispersion of the flour at pH 8.0, subsequent centrifugation, and drying of the supernatant yielded a pea protein concentrate (PPC). Further fractionation was achieved by applying isoelectric precipitation on the supernatant, followed by centrifugation, and re-dispersion, resulting in the globulin-rich fraction (GLB-RF); the supernatant – which could be considered a by-product – was diafiltrated to obtain the albumin-rich fraction (ALB-RF). Size exclusion chromatography showed that PPC contained mostly globulins and some albumins, whereas GLB-RF and ALB-RF indeed contained either globulins or albumins. The smaller and less charged albumins displayed strong in-plane interactions at the air-water interface, thereby forming a stiff and cohesive interfacial layer which led to high foam overrun (258%) and stability (272 min). PPC- and GLB-RF contained larger and highly charged globulins, showing substantially lower foam overruns (<81%) and stability (<70 min), which can be attributed to the formation of weaker and more mobile interfacial layers than ALB-RF. For the emulsifying properties, it was found that the larger size and higher net charge of globulins resulted in the formation of oil droplets that were stable against coalescence and flocculation, while albumin-stabilised oil droplets flocculated due to lower surface charges. The functionality of the fraction is largely determined by the protein composition. We have demonstrated how targeted fractionation can be used to control this composition, and hence the functionality of pea protein fractions. Graphical abstract: Image 1 Highlights: Pea globulins and albumins could be separated by isoelectric precipitation. Albumins showed high foam ability and stability and formed a stiff interface. Globulins dominated the foaming behaviour of a globulin and albumin mixture. Pea globulins formed more stable emulsions than pea albumins. Fractionation can be optimized to yield good foaming and emulsifying agents.